Pengelolaan Tanah Tegakan Jambu Mete Melalui Penerapan Model Usahatani Ekologis Terpadu Di Dusun Lendang Mamben Desa Anyar Bayan Lombok Utara - Ngawit, I Ketut; Jayaputra, Jayaputra; Azhari, Anjar Pranggawan; Jihadi, Amrul (Universitas Mataram, 2025)
Cashew tree plantations often experience fallow periods, causing the soil layer to be more easily eroded. As a result, the process of decreasing land productivity is happening more quickly. The right action to overcome this problem is to utilize the reciprocal relationship between plants and livestock to form an integrated ecological farming model. The purpose of this activity is to improve farmers' knowledge and skills in managing cashew nut plantations by implementing integrated ecological farming, processing agricultural waste, weeds and other forage for animal feed, and processing manure and livestock waste into organic fertilizer. The approach method used is participatory action in the form of direct training and assistance in the field from May 5, 2024 to November 6, 2024. The results of the activity showed that the implementation of training and mentoring for the application of integrated ecological farming models on cashew nut stands took place in an orderly, safe and smooth manner. The knowledge and skills of members of the Tunas Mekar farmer group, Lendang Mamben hamlet, Anyar Village, Bayan, North Lombok increased, as evidenced by their high participation, enthusiasm and enthusiasm in following the entire series of activities. The cultivation of peanuts and corn crops resulted in higher income and profits for farmers compared to the cultivation of long beans. In addition to being able to provide higher profits, the average BC-ratio for cultivating these two types of crops is also relatively higher compared to cultivating long beans, namely 2.81 for corn and 2.67 for peanuts